Kepuasan Kerja Para Aparatur Sipil Negara (ASN) di Pemko Padang yang Mengalami Job Mismatch Berdasarkan Usia dan Pendidikan - Yani, Diah Sukma; Nurmina, Nurmina (Lembaga Yasin AlSys, 2024)
Employees who match their jobs have a much higher level of job satisfaction than employees who experience a mismatch with their jobs. Several studies say that a mismatch between education and work can have an impact on low levels of job satisfaction and make mismatch one of the factors that influences a person's job satisfaction. Based on several studies, the results show that job satisfaction is influenced by two things, namely work factors and individual factors, for example age and education. Government services have the highest level of nonconformity, namely 74.24%. Based on the data that has been explained, it is known that there is data on job qualification discrepancies in Indonesia, especially in the government sector. The aim of this research is to determine the differences in job satisfaction of state civil servants in the Padang City Government who experience job mismatch based on age and education. This research was studied using quantitative research with a comparative approach. Data collection was carried out using a Google form by distributing the barcode scan questionnaire link via WhatsApp social media and the Google Leans application. The data analysis technique for this research uses the two way anova test. The results obtained in this research show that there is no difference in job satisfaction of Padang City Government ASN who experience job mismatch based on age and education.